2012
DOI: 10.3174/ajnr.a2979
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of MR Imaging Findings in Wernicke Encephalopathy: Are Atypical Areas of Involvement Only Present in Nonalcoholic Patients?

Abstract: BACKGROUND AND PURPOSE:Although MR imaging is considered the most effective method to confirm a diagnosis of WE, MR imaging studies designed to distinguish WE between NA and AL patients have yielded controversial results. The purpose of this study was to determine potential differences in MR imaging features between AL and NA patients with WE and to compare neurologic symptoms with MR imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…As an answer to this hypothesis, in 2010, Hygino da Cruz and his collaborators reported two cases of nonalcoholic WE demonstrating that both typical and atypical MR imaging findings may coexist [83]; in the same year, Sugai and Kikugawa added their experience describing atypical MRI findings in two patients with WE, both of whom were alcoholic [84]. In 2012, Ha et al reported MR imaging findings of twenty-four patients (13 AL and 11 NA) with WE showing that the atypical MR imaging findings, including cerebral cortex and cranial nerve nuclei lesions, were present both in the AL group and in the NA group [85]. Few months later, Liou et al described an interesting case of an AL patient affected by WE that showed lesions in olivary bodies, brain stem cranial nerve nuclei, and the dentate nuclei of cerebellum in absence of hyperintense lesions in the typically affected areas [86].…”
Section: Mr Imaging Findingsmentioning
confidence: 99%
“…As an answer to this hypothesis, in 2010, Hygino da Cruz and his collaborators reported two cases of nonalcoholic WE demonstrating that both typical and atypical MR imaging findings may coexist [83]; in the same year, Sugai and Kikugawa added their experience describing atypical MRI findings in two patients with WE, both of whom were alcoholic [84]. In 2012, Ha et al reported MR imaging findings of twenty-four patients (13 AL and 11 NA) with WE showing that the atypical MR imaging findings, including cerebral cortex and cranial nerve nuclei lesions, were present both in the AL group and in the NA group [85]. Few months later, Liou et al described an interesting case of an AL patient affected by WE that showed lesions in olivary bodies, brain stem cranial nerve nuclei, and the dentate nuclei of cerebellum in absence of hyperintense lesions in the typically affected areas [86].…”
Section: Mr Imaging Findingsmentioning
confidence: 99%
“…The presence of diffusion restriction most strongly suggests arterial stroke, toxicity, infection, or, to a lesser degree, lymphoma or deep venous thrombosis. 1,2,4, [25][26][27]35,39,42,45,50,57,60,70,90 Conversely, diffusion restriction has not been found in patients with dAVF-induced thalamic dementia. Strong gadolinium enhancement is most consistent with a high-grade neoplasm; 26,27,58 however, other conditions including dAVFs can also have some degree of gadolinium enhancement.…”
Section: Thalamic Dementia Syndrome: Differential Diagnosis and Workupmentioning
confidence: 99%
“…In WE, signal-intensity alterations in the cranial nerve nuclei are less common. 1 To our knowledge, this is the first report of WE with an abducens nucleus-confined lesion on magnetic resonance imaging. When Miller-Fisher syndromelike symptoms are encountered, physicians should consider the possibility of WE and carefully evaluate the presence of signal intensity alterations in the cranial nerve nuclei.…”
mentioning
confidence: 70%
“…In WE, signal‐intensity alterations in the cranial nerve nuclei are less common . To our knowledge, this is the first report of WE with an abducens nucleus‐confined lesion on magnetic resonance imaging.…”
mentioning
confidence: 99%